Determinants of non-interest income in Malaysian banking industry : a comparative analysis on CIMB and RHB bank - Baskaran, Meyappan (2017)
We have analysed the determinants of non-interest income among banking industry in Malaysia. A comparative analysis between CIMB Bank and RHB Bank has been conducted from the period of 2004 till 2015. The main objective of this study is to identify the relationship between non-interest income of CIMB Bank and RHB Bank with factors such as bank size, total loan, total equity, net interest margin and inflation in the short run and long run. This study employs time series analysis techniques such as Vector Error Correction Model (VECM), Johanssen Co-Integration Analysis and Forecast Error Variance Decomposition (FEVD) Analysis to identify the relationship among variables in the short run and long run. Based on our analysis bank size, total equity capital, net interest margin and inflation are the significant factors determine non-interest income of CIMB Bank whereas only bank size and net interest margin are the significant factor determines non-interest income of RHB Bank in the long run. According to FEVD analysis in the short run, total loan is the only significant factor in determining the non-interest income of CIMB Bank whereas bank size and inflation are the significant factor determining the non-interest income of RHB Bank. This study finds that each bank has their unique determinants of non-interest income. Both in the long run and short run the determinants of non-interest income differ between CIMB Bank and RHB Bank. The determinants of non-interest income differ between the banks may be due to policy of the banks towards non-interest business or the types of noninterest products the banks involved in. The findings are consistent with the industry expert opinion where banks are increasing their share of non-interest income in the areas which they have additional strength and competitive advantage